Korpusowa analiza dyskursu związanego z tematyką imigracji w brytyjskiej prasie opiniotwórczej (Conversatoria Linguistica, 2019)
The aim of the paper is to show the applicability of corpus–driven meth-odology to media discourse analysis. Theoretically, the study assumes that the se-mantic meaning of a lexical item is emergent and distributed, i.e. it resides in the word under investigation as well as the collocations with which it co-occurs. Meth-odologically, the analysis is primarily quantitative and relies on automatic data ex-traction and statistical calculations. The data used for the study were gleaned from a corpus of the British press, which contains articles coming from three broadsheet newspapers representing both a conservative and a left–wing political stance. The paper demonstrates how a corpus–driven methodology can be successfully em-ployed in media studies, in particular in press discourse analysis.